A CO2‐gas precursor to the March 2015 Villarrica volcano eruption. (14th June 2017) - Aiuppa, Alessandro; Bitetto, Marcello; Francofonte, Vincenzo; Velasquez, Gabriela; Parra, Claudia Bucarey; Giudice, Gaetano; Liuzzo, Marco; Moretti, Roberto; Moussallam, Yves; Peters, Nial; Tamburello, Giancarlo; Valderrama, Oscar. A.; et al.
Abstract: We present here the first volcanic gas compositional time‐series taken prior to a paroxysmal eruption of Villarrica volcano (Chile). Our gas plume observations were obtained using a fully autonomous Multi‐component Gas Analyser System (Multi‐GAS) in the 3 month‐long phase of escalating volcanic activity that culminated into the 3 March 2015 paroxysm, the largest since 1985. Our results demonstrate a temporal evolution of volcanic plume composition, from low CO2 /SO2 ratios (0.65‐2.7) during November 2014‐January 2015 to CO2 /SO2 ratios up to ≈ 9 then after. The H2 O/CO2 ratio simultaneously declined to <38 in the same temporal interval. We use results of volatile saturation models to demonstrate that this evolution toward CO2 ‐enriched gas was likely caused by unusual supply of deeply sourced gas bubbles. We propose that separate ascent of over‐pressured gas bubbles, originating from at least 20‐35 MPa pressures, was the driver for activity escalation toward the 3 March climax. Key Points: We present the first volcanic gas compositional time‐series taken prior to a paroxysmal eruption of Villarrica volcano (Chile) We find evidence for a gas CO2 /SO2 ratio precursor to eruption of a carbon‐poor arc magma We interpret preeruptive evolution toward CO2 ‐enriched gas as caused by supply of deeply sourced gas bubbles